2018
DOI: 10.1016/j.jhin.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

High reproduction number of Middle East respiratory syndrome coronavirus in nosocomial outbreaks: mathematical modelling in Saudi Arabia and South Korea

Abstract: R for the nosocomial MERS outbreaks in KSA and South Korea was estimated to be in the range of 2-5, which is significantly higher than the previous estimate of <1. Therefore, more comprehensive countermeasures are needed to address these infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
1
46
0
Order By: Relevance
“…While many epidemiological features of SARS-CoV-2 still need to be resolved, there are many features of transmission that appear to align more with MERS-CoV than SARS-CoV. One component of transmission is the reproductive number (R 0 ), which is currently thought to be approximately 2.0-3.0 for SARS-CoV-2, broadly in line with than for SARS-CoV, and while MERS-CoV has a low R 0 in humans (b 1), it is high in camels and in outbreak situations (N 3) [69][70][71][72][73]. Another study has reported that the serial interval (time from the disease onset in a patient to the onset of the disease in secondary case) can be estimated to be below 4 days, suggesting that transmission can occur before the onset of clinical signs [74].…”
Section: Discussionmentioning
confidence: 99%
“…While many epidemiological features of SARS-CoV-2 still need to be resolved, there are many features of transmission that appear to align more with MERS-CoV than SARS-CoV. One component of transmission is the reproductive number (R 0 ), which is currently thought to be approximately 2.0-3.0 for SARS-CoV-2, broadly in line with than for SARS-CoV, and while MERS-CoV has a low R 0 in humans (b 1), it is high in camels and in outbreak situations (N 3) [69][70][71][72][73]. Another study has reported that the serial interval (time from the disease onset in a patient to the onset of the disease in secondary case) can be estimated to be below 4 days, suggesting that transmission can occur before the onset of clinical signs [74].…”
Section: Discussionmentioning
confidence: 99%
“…60 The reproduction number for nosocomial outbreaks in Saudi Arabia and South Korea was estimated to be between two and five. 61 The risk factors for nosocomial MERS-CoV outbreaks are summarised in panel 4. [28][29][30][31]36,[47][48][49]52,56…”
Section: Severity Of Illness and Transmissionmentioning
confidence: 99%
“…1C). Median age of asymptomatic cases was 34 (IQR, [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48], the majority of whom were females (70%, n = 47/67) and had no underlying co-morbid conditions (78%, n = 29/37). The proportion of HCP among asymptomatic infections was high (70%, n = 47/67), and the CFR was null.…”
Section: Resultsmentioning
confidence: 99%